Studying the status quo of double bass teaching and compile technical guide in Nanchang University, Jiang xi province, China - Liu Xi; Yodwised , Chutasiri; Srisombut, Rujee (Journal of Modern Learning Development, 2023)
The objectives of this experimental study were: (1) To study the current situation of double bass teaching, (2) To compile a double bass teaching guide, (3) To teach students with the double bass teaching guide, (4)To assess students' abilities and outcomes. During the semester from March 2022 to July 2022, the population is the double bass major of Nanchang University, China, with 15 people. The sample used a purposeful, systematic sampling technique to select first- and second-year students, a total of 9 people (ages 18-20) who are interested in the technical guide and willing to try it. This study will provide a technical guide to the double bass for students to learn and collect data through observation records. The research tools are (1) a Double bass teaching guide, (2) a lesson plan with 10 lessons, (3) an assessment sheet, and an interview sheet. The statistic used to analyze the data is the percentage. The findings were: The viewing and use of the double bass teaching guide are helpful for non-conservatory students to improve their basic skills as an auxiliary tool in studying professional courses and how to use learning tools to make students' learning motivation and reflection creative and active. The teacher's assessment with the teaching guide is 91%, which means that the teacher is very effective in examining and using the double bass teaching guide. Students pass the exam with an average score of 27, which means they are doing well.